ASSESSING THE LEVEL OF RELIABILITY OF CHATGPT AS A TRANSLATION ASSISTANCE TOOL FOR TRANSLATION STUDENTS - Sura Jarjis Wadeea (Academic Journal Research, 2026)
Objective: This paper explores the role of ChatGPT as a learning tool, focusing on students' reliance on it for completing translation assignments and aims to assess the extent to which students depend on ChatGPT for translations. Method: The study was conducted using a questionnaire given to fourth-year students in the Translation Department, with students instructed to use ChatGPT for their translation tasks. The study also compares the translation outcomes of students using Arabic and English commands for ChatGPT, alongside students' awareness of the proper way to use ChatGPT. Results: The findings suggest that there were no noticeable differences in the quality of translations whether students used Arabic or English to prompt ChatGPT. The students' specification of the translation type (general or legal) did not result in significant variations in the output. However, students were found to need guidance on how to properly interact with ChatGPT to obtain specific or accurate translations. Novelty: The study highlights the need for students to learn the correct way to use AI tools like ChatGPT, particularly for specialized translations, and points out that while ChatGPT is a useful tool, it does not consistently provide accurate specialized terms or phrases. This insight is crucial for understanding AI's limitations in educational settings and encourages the development of proper usage practices.